Reality group counseling in addressing client problems - Gusti Rahayu; Neviyarni Suhaili; Netrawati Netrawati (Counseling and Humanities Review, 2021)
Every individual has a fundamental desire to fulfill his basic needs. When what he wants has been fulfilled indirectly his conditions have been satisfied. On the other hand, if the desire cannot be fulfilled by reality, the individual will feel pressured and stressed, causing a difference in what he wants with what he gets and causing problems for the individual. Reality counseling has the aim of helping individuals align what they want with what happens or is obtained by the reality of the individual's life.